Shock Index and Associated Factors in Trauma Patients Admitted at a Referral Hospital in Harare, Zimbabwe - Mukona, Doreen; Mukahanana, Cecilia; Zvinavashe, Mathilda (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Background- Trauma causes significant morbidity and mortality worldwide. It impacts physically, economically, and socially on individuals, communities, and countries at large. Purpose- To examine association between shock index (SI) and clinical outcomes in trauma patients. Methods- A retrospective descriptive analytical study conducted on a random sample of 120 records of trauma patients. A clinical audit form was used. Data were analysed using SPSS VS 20. Descriptive statistics were used to analyse demographic data, vital signs, causes of injury, and clinical outcomes of trauma while Chi-square was used for associations between shock index and demographic variables and causes of injury. Logistic regression was done to examine the association between SI and clinical outcomes of trauma. Results- Mean age of participants was 39.64 years. Prevalence of abnormal shock index was 41.67%. Only demographic data and place of residence were associated with abnormal shock index (p>0.05). SI was significantly associated with haemorrhage ((p>0.009), OR-, 0.26, confidence interval (CI)- 0.012-0.58) and shock ((p>0.0127, OR-0.27, CI-(0.10-0.76)). Conclusion- Prevalence of abnormal SI was high. It is an easy-to-use tool that is very efficient in emergencies to predict need for aggressive resuscitative therapy and to determine prognosis